Percutaneous closure of patent foramen ovale: impact of device design on safety and efficacy. Issue 2 (16th January 2004) - Schwerzmann, M; Windecker, S; Wahl, A; Mehta, H; Nedeltchev, K; Mattle, H; Seiler, C; Meier, B
Abstract : Objective: To compare the safety and efficacy of percutaneous closure of patent foramen ovale (PFO) with the Amplatzer PFO occluder (Amplatzer) or the PFO STAR device (STAR) in patients with presumed paradoxical embolism. Methods: Implantation characteristics, procedural complications, residual shunt, and recurrence of thromboembolic events were recorded prospectively in 100 consecutive patients undergoing percutaneous PFO closure with the STAR (n  =  50) or Amplatzer (n  =  50) devices between 1998 and 2001. The study was not randomised. Device implantation was successful in all cases. Results: There were more procedural complications in the STAR than in the Amplatzer group (8/50 v 1/50, p  =  0.01). More than one device placement attempt was an independent predictor of procedural complications (odds ratio (OR) 8.5, 95% confidence interval (CI) 1.3 to 55.8; p  =  0.03). A residual shunt six months after PFO closure, assessed by transoesophageal contrast echocardiography, occurred more often in the STAR than the Amplatzer group (17/50 v 3/50, p  =  0.004), and was predicted in the STAR group by the use of a device with a 5 mm as opposed to a 3 mm disc connector (OR 6.1, 95% CI 1.1 to 34.0; p  =  0.04). The actuarial risk of recurrent thromboembolic events after 3.5 years was 16.8% (95% CI 7.6% to 34.6%) in the STAR and 2.7% (95% CI 0.4% to 17.7%) in the Amplatzer group after three years (p  =  0.08). Conclusions: Percutaneous PFO closure with the Amplatzer PFO occluder had fewer procedural complications and was more likely to be complete than with the STAR device. These findings underline the importance of device design for successful percutaneous PFO closure.